(untitled) (Revista de Ciências Agroveterinárias, 2014)
The paper aims to show the utility of using anaglyph on the demarcation of soil mapping units; facilitating identification and enabling the expansion of information collection and observation points for larger areas. The use of photo-interpretation signifcantly reduces the time it would spend in recognition of all the properties and limits in the field. The work was conducted with the use of anaglyph in semi-detailed soil survey of the Lajeado dos Mineiros Watershed, in São José do Cerrito, Santa Catarina, covering an area of 2.877,37 ha. Data for soil classification was obtained through observation and collection in the field. The map of delineation of mapping units was produced using a scale of 1:50,000.